Power Quality Enhancement in PV integrated System Using GSA-FOPID CC-VSI Controller - Srikanth Goud, B.; Naga Sai Kalyan, CH.; Krishna, D.; Nagi Reddy, B.; Bajaj, Mohit; Choudhury, Subhashree; Shukla, Swati (EAI Endorsed Transactions on Scalable Information Systems, 2023)
Over the past ten years, a lot of effort has been made to promote the broad adoption of renewable energy. This has led to a push to generate electricity from renewable resources like wind and solar. However, power quality (PQ) concerns may arise from incorporating these renewable energy sources into the system. Researchers have so been working on new methods for addressing PQ problems. Most of the methods described in the literature deal only with one particular kind of PQ problem. However, PQ concerns have gotten increasingly serious owing to the extensive integration of various renewables into the distribution system. In this research, we provide a formalisation of the PQ problem as an optimisation problem and suggest an implementation of the Genetic Search Algorithm (GSA) to address it. Harmonic distortion, power loss, and voltage are used as metrics for success. Simulation in MATLAB/Simulink is used to analyse the proposed system and compare it to a standard PI controller. When combining renewables to Grid Connected System, the proposed GSA-based FOPID control system efficiently reduces the impact of PQ concerns and keeps the output power where it needs to be.